Investment justification of advanced manufacturing technology: a review. (1st December 2006) - Narain, Rakesh; Yadav, R.C.; Sarkis, Joseph
This paper reviews a wide range of literature on the investment justification of Advanced Manufacturing Technologies (AMTs). It provides an updated and a comprehensive perspective of the issues surrounding the problem of investment justification of AMT and provides some direction for future research such as the design and development of standard modules of the hardware elements comprising AMT, the need to popularise the use of Activity-Based Costing (ABC) systems, and pooling information from different users of AMT across the globe, which could be used for technology appraisal and also for ascertaining the expected benefits from a certain level of technology. As well, evolutionary characteristics and future directions of AMT appraisal and justification approaches are described with research directions identified.